TR—Temporal Reasoner - Chai, Quek; Abdul Rahman, Abdul Wahab; Wee-Chee, Sim (Elsevier, 1996)
A constraint-based qualitative reasoning system that integrates Allen's interval calculus, point calculus and part of Simmons' quantity lattice is presented in this paper. The highlight of the work is a simple but powerful logical system for expressing both quantitative and qualitative information managed by a temporal manager (TM). Allen's algorithm, which deals with time intervals, is extended to reason about time points. The hybrid method of propagating temporal constraints permits flexible control over both systems. We try to offset the limitations of an interval-based representation by the advantages of a point-based representation.